Upaya Pencegahan Tindak Pidana Begal di Wilayah Kepolisian Resor Bangkalan (Lex Journal : Kajian Hukum dan Keadilan, 2024)
Violent theft (Begal) is a type of crime that has become a serious concern in the criminal justice system. One area that is notorious for Begal is the island of Madura, specifically in the district of Bangkalan, where it has become common knowledge that Begal has spread widely in recent years. This is what prompted the author to conduct this research with the following objectives: 1. To analyze the factors contributing to the occurrence of Begal crimes. 2. To identify the efforts made by law enforcement authorities, specifically the police, to prevent Begal crimes. The research employs a socio-legal methodology. The results of the research conducted indicate that Begal crimes in the Bangkalan Police District, influenced by economic, environmental, educational, and drug-related factors, pose a significant challenge to law enforcement. The Bangkalan Police District has implemented preventive, repressive, and curative measures, such as routine patrols, vehicle operations, CCTV installation, education, and rehabilitation of offenders. These measures have successfully reduced the number of begal cases over the past three years, demonstrating the effectiveness of collaboration between the police and the community.